G279(P) In situ repeated simulation training in paediatric departments improves treatment times and reduces latent errors. (May 2019) - Gaiottino, J; Parbery-Clark, C; Lee, M; Le Geyt, J; Halbert, J; Williams, B
Abstract : Background: Simulation based medical education can be a powerful tool in practising communication and teamwork as well as strengthening technical and clinical skills [1] . There is growing evidence that simulation training spaced at regular intervals can improve clinical knowledge, including in paediatric acute illness management [2] . In situ, high-fidelity simulation also allows identification of errors inherent to the work environment [3, 4] . Aim: To determine whether repeated simulation based training improves time to key outcomes in common paediatric emergency and decreases the number of latent errors in paediatric departments. Methods: Five paediatric emergency scenarios were used in simulation training of clinical staff in Myanmar and the UK. A structured interactive debriefing tool was used before repeating the scenario with the same clinical lead. The latent errors and times to key treatment points were recorded. Results: The overall average reduction in time to key treatment steps was 88 s (p=0.04; 95% CI 7–190) in the UK hospital and 74 s (p=0.045; 95% CI 3–144) in the Myanmar hospital. There was an 83% and 59% decrease in the number of latent errors in the UK and Myanmar hospitals respectively. Conclusion: Repeated simulation based training in both settings showed a shortened time to key treatment steps in paediatric emergency scenarios and a decrease in the overall number of latent errors identified which would enhance patient safety through improved management of critically unwell children.